Topical issues of legal regulation of medical humanitarian care in a pandemic - O. E. Karpov; D. N. Nikitenko; V. V. Tretyakov; D. S. Voronov (Управление)
The article is devoted to the scientific understanding of the practical aspects of receiving, customs declaration and use of humanitarian aid in the Russian Federation in the context of a pandemic of the new coronavirus infection COVID-19. The procedure for interaction of a medical organization as a recipient of humanitarian aid with executive authorities and international donors of gratuitous aid has been considered in detail and outlined. The rapid spread of the new coronavirus infection COVID-19 in the world did not provide an opportunity to prepare special measures to regulate legal relations within the framework of humanitarian assistance in the Russian Federation. At the same time, the receiving organization was faced with the task of promptly transferring humanitarian aid to the final recipients in order to prevent the spread of a new coronavirus infection in the Russian Federation. The authors studied the issues of receiving, declaring and transferring humanitarian aid to the final recipients in a pandemic COVID-19, identified collisions of existing legal norms and suggested possible options for improving the system for receiving and distributing humanitarian aid. The necessity of developing and adopting a normative act that comprehensively regulates the procedure for organizing, preparing and receiving humanitarian aid, the procedure for its acceptance with verification of the availability of quantity, compliance, labeling, packaging, technical documentation, as well as its compliance with other requirements, has been proved.The article substantiates expediency of the introduction of amendments to some norms of customs regulation, envisaging the possibility of transferring cargo placed under a special customs procedure to other persons according to the decision of the authorized executive body.The relevance and high practical significance of the article is caused by the need for the timely distribution of large  volumes of humanitarian aid in order to effectively prevent and eliminate the consequences of emergencies.